Odpowiedź:
[tex]a)\ \ 1\frac{1}{4}-\frac{1}{2}-\frac{3}{8}+1\frac{5}{8}=1\frac{1}{4}-\frac{1}{2}+1\frac{2}{8}=1\frac{1}{4}-\frac{1}{2}+1\frac{1}{4}=2\frac{2}{4}-\frac{1}{2}=2\frac{1}{2}-\frac{1}{2}=2\\\\\\b)\ \ (7\frac{3}{5}-2\frac{7}{10})-(3\frac{1}{4}+1\frac{1}{2})=(7\frac{6}{10}-2\frac{7}{10})-(3\frac{1}{4}+1\frac{2}{4})=(6\frac{16}{10}-2\frac{7}{10})-4\frac{3}{4}=\\\\=4\frac{9}{10}-4\frac{3}{4}=4\frac{18}{20}-4\frac{15}{20}=\frac{3}{20} [/tex]
[tex]c)\ \ 12-(2\frac{1}{5}+3\frac{3}{4})=12-(2\frac{4}{20}+3\frac{15}{20})=12-5\frac{19}{20}=11\frac{20}{20}-5\frac{19}{20}=6\frac{1}{20} [/tex]